Physicochemical and sensory analysis of surimi sausage incorporated with rolled oat powder subjected to frying - Muzamil, Muhamad Zarulakmam; Mohamad Razali, Umi Hartina; Mohd Noor, Nor Qhairul Izzreen; H.Z., Nabila; W., Wafin; Mat Yusoff, Masni; Mohammad Rashedi, Ismail Fitry; Ashari, Rozzamri (Faculty of Food Science and Technology,Universiti Putra Malaysia, 2021)
In the present work, the effects of rolled oat powder (ROP) incorporated into surimi sausage on the physicochemical and sensory attributes of sausage were investigated. The incorporation of ROP into surimi sausage significantly increased moisture content, protein content, and water holding capacity, but decreased shrinkage and cooking loss. The incorporation of ROP was also able to significantly decrease fat absorption during frying. However, increased amount of ROP caused a significant decrease in texture especially after frying. Although a decrease in texture was recorded, the sensory analysis score did not display any significant difference on the colour, hardness, and overall acceptability of the surimi sausage. The development of surimi sausage incorporated with ROP could be an approach to utilise fish as a commodity, and produce a healthier and more nutritious sausage even after frying.